THERAPEUTIC EFFICACY OF QUERCETIN IN PATIENTS WITH ARTERIAL HYPERTENSION AND METABOLIC SYNDROME - Bilovol, O.M.; Kniazkova, I.I.; Kuzminova, N.V.; Kirienko, O.M.; Abramova, L.P.; Gavrylyuk, A.O. (World of Medicine and Biology, 2020)
The purpose of our research was to increase the effectiveness of the therapy of the patients with hypertension and metabolic syndrome. 56 patients with hypertension, and metabolic syndrome were examined. After registration of the baseline data in addition to baseline therapy Quercetinum 40 mg 3 times a day for 2 months was administered to 30 patients (group 1). Basic therapy was administered to 26 patients (group 2). After treatment in group 1, the levels of office systolic and diastolic blood pressure were 7.6 % and 6.9 % (p
Keywords: hypertension; metabolic syndrome; lipid peroxidation; tumor necrosis factor-α; quercetin